Small-Molecule Compound CY-158-11 Inhibits Staphylococcus aureus Biofilm Formation - Li Shen; Jiao Zhang; Yao Chen; Lulin Rao; Xinyi Wang; Huilin Zhao; Bingjie Wang; Yanghua Xiao; Jingyi Yu; Yanlei Xu; Junhong Shi; Weihua Han; et al. (Microbiology Spectrum, 2023)
ABSTRACT Staphylococcus aureus is an important human pathogen and brings about many community-acquired, hospital-acquired, and biofilm-associated infections worldwide. It tends to form biofilms, triggering the release of toxins and initiating resistance mechanisms. As a result of the development of S. aureus tolerance to antibiotics, there are few drugs can availably control biofilm-associated infections. In this study, we synthesized a novel small-molecule compound CY-158-11 (C22H14Cl2NO2Se2) and proved its inhibitory effect on the biofilm formation of S. aureus at a subinhibitory concentration (1/8 MIC). The subinhibitory concentration of CY-158-11 not only did not affect the growth of bacteria but also had no toxicity to A549 cells or G. mellonella. Total biofilm biomass was investigated by crystal violet staining, and the results were confirmed by SYTO 9 and PI staining through confocal laser scanning microscopy. Moreover, CY-158-11 effectively prevented initial attachment and repressed the production of PIA instead of autolysis. RT-qPCR analysis also exhibited significant suppression of the genes involved in biofilm formation. Taken together, CY-158-11 exerted its inhibitory effects against the biofilm formation in S. aureus by inhibiting cell adhesion and the expression of icaA related to PIA production. IMPORTANCE Most bacteria exist in the form of biofilms, often strongly adherent to various surfaces, causing bacterial resistance and chronic infections. In general, antibacterial drugs are not effective against biofilms. The small-molecule compound CY-158-11 inhibited the biofilm formation of S. aureus at a subinhibitory concentration. By hindering adhesion and PIA-mediated biofilm formation, CY-158-11 exhibits antibiofilm activity toward S. aureus. These findings point to a novel therapeutic agent for combating intractable S. aureus-biofilm-related infections.